Attenuation of Pain Perception Induced by the Rubber Hand Illusion - Fang, Wen; Zhang, Ruyuan; Zhao, Yijie; Wang, Liping; Zhou, Yong-Di (Frontiers in Neuroscience, 2019)
Adaptive behavior usually requires accurate representations of body positions and ownership, which rely on integration of multiple sources of sensory information. The rubber hand illusion (RHI) presents a compelling example demonstrating that the combination of visual and tactile signals strongly influences the subjective experience of body ownership. However, it still remains unclear how the perception of body ownership in turn alters other aspects of sensory processing, such as pain perception. In the present study, we examined whether the RHI could modulate the subjective experience of pain. We set three conditions corresponding to different levels of ownership of the rubber hand: the synchronous condition in which the rubber and the real hand were simultaneously stroked; the asynchronous condition in which the two hands were asynchronously stroked; the own-hand-only condition in which only the real hand was stroked. Results from our pilot experiment indicated that subjects experienced the stronger RHI in the synchronous condition, compared with the strength of RHI in the other two conditions. In the main experiment, subjects were requested to report the intensity and unpleasantness of pain evoked by laser stimuli under the three stroking conditions. Results showed that pain ratings were significantly lower under the synchronous condition than those under the other two conditions, suggesting the RHI could induce a significant analgesic effect. Furthermore, the correlation analysis showed that the degree of the analgesic effect was positively correlated with the RHI strength across individuals. Taken together, these results suggest an analgesic effect of the RHI and support the potential usage of visual illusions in future translational research on pain.